Exploring strategies for translating technical texts - Huang, Qianqian (Nanyang Technological University, 2023)
Global hydrogen development has gained its momentum in recent years. Both Singapore and China have announced national plans for developing low-carbon hydrogen, which has been identified as a potential pathway to reduce carbon dioxide emissions. Moreover, the two countries value international cooperation and have signed agreements to collaborate in renewable energy. This capstone project has chosen Singapore’s National Hydrogen Strategy as the Source Text (ST) and produced a Chinese translation adopting a “technical skopos” approach. During the translation process, the translator has identified major challenges for technical translation, and explored strategies or techniques that can be used to overcome the challenges and improve the quality of technical translation.